Optimizing the CSP-Calcium Looping integration for Thermochemical Energy Storage. (15th March 2017) - Alovisio, A.; Chacartegui, R.; Ortiz, C.; Valverde, J.M.; Verda, V.
Highlights: Several CSP-CaL configurations are analyzed for thermochemical energy storage. A pinch-analysis has been carried out in order to estimate the best integration. High CSP plant efficiency could be achieved using a closed CO2 Brayton power cycle. Abstract: Thermochemical energy storage (TCES) is considered a promising technology to overcome the issues of intermittent energy generation in Concentrated Solar Power (CSP) plants and couple them with yearly electricity demand. The development of this technology could favor the commercial deployment of CSP, which is considered as a key factor for new challenges in reducing GHG emissions. Among other possibilities, using the Calcium Looping (CaL) process for TCES is an interesting choice mainly due to the low cost of natural CaO precursors such as limestone (below 10/ton) and the high energy density that can be achieved (around 3.2 GJ/m 3 ). This manuscript explores several configurations in order to maximize the performance of the CSP-CaL integration with the focus on power cycle integration in the carbonator zone. For this purpose, firstly, a discussion about the possibility of using open and closed power cycles is carried out, which leads to the conclusion that a CO2 closed cycle is more appropriate. Then, a closed regenerative CO2 Brayton cycle is analyzed in further detail and optimized by means of the pinch-analysis methodology. A main output is that high plant efficiencies (of about 45%) can be achieved using a simple closed CO2 Brayton power cycle. The optimized integration layout shows good performances at carbonator to turbine outlet pressure ratios around 3, thus allowing for a feasible integration of the power cycle in the CSP-CaL system.